Agreements against competition in the telecommunications sector - comparative legal study - األسخاذ امدكخِر ًاصر خنٔل جالل; المدرس المساغد سرةسج كادر حسٔي (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
There is no doubt that competition plays a major role in the development of trade and the national economy. Therefore, it has been of great importance in the countries that adopt the principle of free economy. This is the importance of issuing laws that regulate competition and protect them from harmful practices by banning these practices and imposing sanctions. Legal procedures, as well as the establishment of special bodies to regulate competition and prevent monopoly and protect them from such practices stipulated in those laws, for example. And because the anti-competitive agreements, which are one of these practices, negatively affect the market and hinder competition as it goes without targeting a particular trader, it aims to reduce competitors or eliminate them through the monopoly of the market and thus harm the national economy and consumers Together, we discussed this study in the telecommunications sector. The study of these agreements in this sector is characterized by some specialty. There is no doubt that the telecommunications sector is one of the most vital sectors in the economic development of any country and sometimes measured by the degree of development of the country and the extent of the development of this sector and the services that can provide to the community, It is important as a measure of the level of economic and social recovery, because it is a measure of social welfare, meeting and satisfying the basic needs of various segments of society. It is one of the fastest growing sectors, witnessing rapid growth due to accelerated progress. Beside his suitability to achieve Good returns, especially with the competition that open it will lead to prosperity and progress of projects, it is also a driving creative ability to innovate and stimulate creativity ... As the most dangerous obstacle to the free competition that is still the stumbling block for the growth of the markets in the telecommunications sector is the agreements that they have abandoned. Most legislations seek to fight these agreements in order to guarantee freedom of competition in order to create a kind of free competition Illegal restrictions and practices. The importance of studying the competition in the communications sector and the prejudicial practices of Jeddah is relatively recent. The unprecedented changes in the telecommunications sector at the global level date back to the last two decades of the twentieth century. Many government institutions involved in telecommunications networks were privatized and serviced to citizens in most countries of the world, and to benefit from policies that call for the liberalization of telecommunications markets and the opening of competition and guided by the rules of the market in the provision of telecommunications services. Therefore, we dealt with the agreements that violate competition in the telecommunications sector through the laws of communications in comparison, through two subjects, in the first topic we dealt with what these agreements, and the second section we have devoted to the legislative organization of these agreements in comparative laws. In the course of our research, we have reached a number of conclusions, through which we have submitted a number of proposals.